Brazilian elite soccer players: Exploring attentional focus in performance tasks and soccer positions - Tedesqui, R. A. B.; Orlick, T. (The Sport Psychologist, 2015)
The purpose of this study was to qualitatively explore the attentional focus experienced by elite soccer players in different soccer positions and performance tasks of both closed and open skills. No previous studies have explored elite soccer players` attentional skills from a naturalistic and qualitative perspective in such detail. Data collection consisted of individual semistructured interviews with eight highly elite Brazilian soccer players from five main soccer positions, namely goalkeeper, defender, wing, midfielder, and forward. Important themes were positive thinking, performing on autopilot, and relying on peripheral vision. For example, thematic analysis indicated that in tasks where there may be an advantage in disguising one`s intentions (e.g., penalty kick), relying on peripheral vision was essential. Early mistakes were among the main sources of distractions; thus, players reported beginning with easy plays as a strategy to prevent distractions. Implications for applied sport psychology were drawn and future studies recommended.